SÀNG LỌC CÁC CHỦNG VI NẤM Rhizopus sp. SINH TỔNG HỢP LOVASTATIN - CHẤT ỨC CHẾ ENZYM HYDROXYMETHYL GLUTARYL COENZYM A REDUCTASE- PHÂN LẬP Ở VIỆT NAM - Vũ, Thanh Tùng; Trịnh, Minh Việt; Nguyễn, Nhật Linh; Đỗ, Tuấn Mến; Lê, Thanh Hoàng; Nguyễn, Thị Thảo; Lưu, Minh Đức; Nguyễn, Thị Trung; Trần, Thanh Tuấn; Nguyễn, Mạnh Đạt; và c.s. (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
SCREENING OF LOVASTATIN PRODUCTION - AN HMG-CoA REDUCTASE INHIBITOR - BY Rhizopus sp. STRAINS ISOLATED IN VIETNAM In this study, several Rhizopus sp. strains isolated from Vietnamese yeast bread samples were screened for their ability to produce lovastatin, an inhibitor of HMG-CoA reductase, using thin-layer chromatography (TLC). A solvent system of dichloromethane and ethyl acetate (70:30, v/v) revealed that two strains, Rhizopus sp. BMM 313 and Rhizopus sp. 5280, produced lovastatin. This conclusion was supported by the alignment of their TLC bands with a lovastatin standard (Sigma), exhibiting a retention factor (Rr) value of 0.57. Based on colony morphology and microscopic characteristics observed via scanning electron microscopy (SEM), Rhizopus sp. 5280 was reclassified as R. microsporus 5280. High-performance liquid chromatography (HPLC) analysis demonstrated that R. microsporus 5280 achieved the highest lovastatin yield at 34.59 mg/L. To optimize lovastatin production and investigate other secondary metabolites with HMG-CoA reductase inhibitory activity, this strain will be further studied to refine growth conditions and medium composition.